DETECTING FINANCIAL DISTRESS THROUGH LIQUIDITY, LEVERAGE, AND SALES GROWTH - Yosef Dema; Wiwin Prastio (Jurnal Scientia, 2023)
The main reason for a company's financial problems is that it is unable to operate its business to meet its obligations, including short-term liabilities. Examining actual data on the impact of liquidity, leverage, and sales growth on financial hardship is the main goal of this study. Data from companies in the real estate and property sectors that were listed on the Indonesia Stock Exchange between 2016 and 2020 were used in this study. The research sample consisted of 46 businesses with 230 observational data collected over a five-year period. employing multiple linear regression analysis along with the purposive sampling strategy to sample. processing data with SPSS 28.0 for Windows and Microsoft Office Excel. According to the study's findings, financial distress is significantly worsened by sales growth and has a significantly beneficial impact on leverage and liquidity.